The Effect of Progressive Muscle Relaxation on Post Cesarean Section Pain, Quality of Sleep and Physical Activities Limitation (International Journal of Studies in Nursing, 2018)
Background: Pain, sleep disturbances, and physical activity limitation are the most tiresome complains of the women post caesarian section (Cs). Progressive muscle relaxation is a promising intervention for these complains. This study aimed to determine the effect of progressive muscle relaxation technique on post-cesarean section pain, quality of sleep and physical activities limitation. Research design: Randomized controlled clinical trial. Setting: post-partum unit at Damanhour National Medical Institute. Sample: A purposive sample of 80 women undergoing Cs was recruited. Randomization block was done to randomly assign 40 women for the study group and 40 for the control group. Tools: Four tools were used for data collection: structured interview schedule, short-form McGill Pain Questionnaire, Physical activities limitation Questionnaire and Groningen Sleep Quality Scale. Results: After the intervention, PMR significantly decreased pain severity among study group in Pain Rating Index scale, Visual analogue pain scale, and Present Pain Intensity scale compared to the control group. The severe physical activities limitation significantly absent from the entire study group, while it was significantly present among 70% of the control group. About two-thirds (62.5%) of the study group had a good quality of sleep compared to 5% of the control group. Conclusion: PMR significantly decreased pain, improved physical activities and quality of sleep among women after Cs. Recommendation: PMR should be incorporated in the nursing intervention protocols post-Cs.